SUBLETHAL EFFECTS OF THIODON AND EKALUX ON FOOD UTILIZATION, GROWTH AND CONVERSION EFFICIENCY IN THE FISH LEPIDOCEPHALICHTHYS THERMALIS - PALANICHAMY, S.; DEVI, T. MALLIGA; ARUNACHALAM, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1986)
Effects of sublethal concentrations of Ekalux (0.002, 0004, 0 006 and 0.008 ppm) and T (0.001, 00002, 00003 and 0 0004 ppm) on food utilization, growth, conversion efficiency oxygen consumption of Lepidocephalichthys thermalis have been studied. Feeding rate fish reared in pesticide-free water was 409 mg/dry food g fish/day. This rate decreased to and 24.4 mg dry food g fish/day, when reared in 0.008 ppm Ekalux and 0.0004 ppm. Thiodopectively. Conversion efficiency was also low a the highest sublethal concentrations of pesticides. Growth rate which was 1.8 mg dry substanceg fish/day in a fish reared in pest free water decreased 1.0 and 0.4 mg/g fish day in maximum sublethal concentration of Eka Thiodon, respectively. Oxygen consumption rate of the fish decreased by more than 40 increasing concentration of pesticides.